Dynamics of Neutralizing Antibody Titers in the Months After Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (30th September 2020) - Crawford, Katharine H D; Dingens, Adam S; Eguia, Rachel; Wolf, Caitlin R; Wilcox, Naomi; Logue, Jennifer K; Shuey, Kiel; Casto, Amanda M; Fiala, Brooke; Wrenn, Samuel; Pettie, Deleah; King, Neil P; et al.
Abstract: Most individuals infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) develop neutralizing antibodies that target the viral spike protein. In this study, we quantified how levels of these antibodies change in the months after SARS-CoV-2 infection by examining longitudinal samples collected approximately 30–152 days after symptom onset from a prospective cohort of 32 recovered individuals with asymptomatic, mild, or moderate-severe disease. Neutralizing antibody titers declined an average of about 4-fold from 1 to 4 months after symptom onset. This decline in neutralizing antibody titers was accompanied by a decline in total antibodies capable of binding the viral spike protein or its receptor-binding domain. Importantly, our data are consistent with the expected early immune response to viral infection, where an initial peak in antibody levels is followed by a decline to a lower plateau. Additional studies of long-lived B cells and antibody titers over longer time frames are necessary to determine the durability of immunity to SARS-CoV-2. Abstract : After severe acute respiratory syndrome coronavirus 2 infection, neutralizing antibody titers peak about 1 month after symptom onset, then decline about 4-fold over the next 2–3 months, with dynamics typical of immune responses to other respiratory viruses.